Wine tourism and digital marketing strategies in the Vinho Verde Region - Costa, Ana Margarida (2021)
Wine tourism has assumed an important role in the increase of the tourism sector and in the development of wine regions in Portugal and around the world, becoming a strategic segment to reach a target motivated by the wine and gastronomy in a rural environment. This exploratory study aims at defining wine tourism and digital marketing strategies, for the elaboration of a proposal of actions to manage the development of the wine tourism segment in a rural tourism accommodation, in the category of agritourism, located in the Demarcated Region of Vinho Verde, in the north of Portugal. In a first moment, a characterization of the rural tourism accommodation was made. Through the application of semi- structured interviews, a qualitative and exploratory study was carried out on 12 companies adhering to the Vinho Verde route with activities similar to the rural tourism accommodation in study. This study enabled the knowledge of demand and supply, before and after the pandemic declaration by COVID-19, as well as the current and future challenges ofthe sector in the Vinho Verde Region. The results show us that there is still a long work to be developed in the Vinho Verde Region, with half of the interviewees only providing wine tasting activities and visits to the vineyards and winery, showing that there is a big lack in differentiating activities. According to the results, the importance of the contribution ofthe wine tourism segment is emphasized as a strategy to reduce seasonality and consecutively it is becoming an important source of revenue. This study resulted in the elaboration of a strategic plan, composed by a set of wine tourism activities, creation and adherence to new sales channels, communication and dissemination channels (offline and online), with the objective of decreasing the tourism seasonality all over the year and as a consequence increase the revenues and the reputation of the rural tourism accommodation in the region where it operates, also making a positive contribution to the development of wine tourism in the Region of Vinho Verde.